Effect of Components of Gamma Oryzanol on Toll-Like Receptor 4: Receptor Structure-Based Pharmacophore, Hit Identification, and In Silico Evidence - Aasia, Kanwal; Muhammad Hamdi, Mahmood; Mahad, Butt; Hidayat Ur, Rahman; Norhida, Ramli; Saiful Bahri, Talip; Showkat, Ahmad Bhawani (Pharmacognosy Journal (Phcog J.), 2025)
Introduction: Polycystic ovarian syndrome is a leading cause of female infertility. Inflammation has a central role in infertility. Persistent activation of Toll-like receptor 4 contributes to inflammation in PCOS. Gamma-oryzanol consists of esters of ferulic acid combined with phytosterols and triterpene alcohol derivatives of rice bran oil, and is known to have anti-inflammatory effects. However, the structural interaction of different gamma-oryzanol compounds with TLR4 remains unknown. Objectives: The study aimed to investigate gamma oryzanol compounds as hit compounds and inhibitors of Toll-like receptor 4 by developing a pharmacophore model through a receptor structure-based approach coupled with molecular docking studies with the Molecular Operating Environment (MOE) software. Methods: A structure-based pharmacophore model was generated from the co-crystalized structure of the TLR4MD2 complex. Gamma-oryzanol derivatives were evaluated against the constructed pharmacophore model to identify potential hit compounds. The potential hit compounds that satisfied essential pharmacophoric features were subjected to molecular docking with TLR4. Results: The pharmacophore consisted of three characteristics: a hydrogen bond donor, a hydrogen bond acceptor, and a hydrophobic. Cycloartenyl ferulate, 24-methylenecycloartenyl ferulate, Campesteryl ferulate, and β-sitosteryl ferulate were found to be the hit compounds against the generated pharmacophore. The docking experiment showed that Cycloartenyl ferulate had the most potent binding interaction with TLR4 (7.9933), followed by 24-methylenecycloartenyl ferulate (-7.8580), Campesteryl ferulate (-6.1675), and β-sitosteryl ferulate (-5.9673). Conclusion: The present pharmacophore modeling and docking findings predict that gammaoryzanol may bind with the TLR4 ligand binding domain, providing structural insights into their therapeutic potential role as a modulator of the TLR4-mediated inflammatory pathway. These findings provide a theoretical foundation for future in vitro and in vivo validation studies aimed at elucidating the mechanistic basis of gamma-oryzanol’s anti-inflammatory activity in PCOS.